Students’ Perception of Quizziz on Reading Comprehension at One Vocational High School in Jombang - Hadi Putri, Zharifah Arihhana (RETAIN : Journal of Research in English Language Teaching, 2023)
Nowadays, technology is already corporate with most peoples' activities. One example of the use of technology in education is a variety of learning tools that could help a learner achieve a better understanding during the teaching-learning process in the class more efficiently and effectively. One of the learning media tools used in the English learning process is Quizizz. The researcher wants to know students' ideas and experiences using Quizizz in reading comprehension. This study is qualitative research, with ten students from 10th grade at one vocational high school in Jombang as participants. In this study, the researcher used semi-structured interviews. This study's results reveal that most students are already familiar with Quizizz to implement in reading comprehension. They believe that Quizizz is a better learning media to use than traditional media and want to use it in every English lesson. Quizizz has many benefits, such as being easy to use, helping recall material for learning better, and making them feel motivated when they see the ranking leaderboard. Quizizz has drawbacks in the teaching and learning process as well.